Supporting Black and Latino boys in school: A call to action. (September 2020) - Huerta, Adrian H.; Howard, Tyrone C.; Haro, Bianca N.
The educational experiences of Black and Latino males in K-12 are often riddled with unnecessary challenges and stresses that contribute to diminished academic outcomes. Adrian H. Huerta, Tyrone C. Howard, and Bianca N. Haro seek to highlight instead the importance of positive asset-based research and practice efforts focused on supporting Black and Latino male high school students. Based on a yearlong study of more than 200 Black and Latino male youth in six urban high schools in California, they provide recommendations for more effectively studying and supporting this population. The combination of asset-based research and practice drawn from that research is intended to better support, engage, and enhance the educational experiences of Black and Latino male students in K-12 institutions and beyond .